Multicystic dysplastic kidney associated with neonatal hypertension - Kazez, A.; Yilmaz, E.; Serhatlioglu, S.; Saglam, M.; Ozercan, I.H.; Demirbag, M. (My University, 1997)
A right multicystic dysplastic kidney (MCDK) case, which was diagnosed in prenatal period by ultrasonography and developed hypertension three weeks after birth, is presented. During examination for hypertension, plasma renin levels were found to be elevated, and therefore the patient underwent nephroureterectomy at the sixth week. Arterial blood pressure and plasma renin levels returned to normal limits following the operation, and the patient was discharged at good health. With the case presented here, it is intended to emphasize that hypertension may require surgical intervention even in newborn period, although conservative treatment is proposed in MCDK cases without any complications.
Multikistik displastik bobrek ve yenidogan hipertansiyonu birlikteligi
Keywords: Congenital anomalies; Kidney; Prenatal diagnosis